Selective production of C9 monomeric phenols via hydrogenolysis of lignin using Pd-(W/Zr/Mo oxides)-supported on biochar catalyst - Gurrala, Lakshmiprasad; Kumar, M. Midhun; Sharma, Shweta; Paek, Changyub; Vinu, R. (Fuel, 2022)
Valorizing lignin to phenolic monomers and fine chemicals is an essential component of a sustainable biorefinery that uses lignocellulosic feedstocks. In this study, Pd-metal oxides (ZrO2, WOx, MoO3) supported on activated biochar (ABC) catalysts were developed for hydrogenolysis of lignin. The metals (2% Pd, 5% Zr, 5% W, 5% Mo) were supported on activated biochar using the wetness impregnation method, and the catalysts were extensively characterized. The effect of addition of secondary metals on active surface properties such as acidity, Pd metal particle size and dispersion were also evaluated. The selectivity to C9 monomeric phenols followed the trend: 2Pd-5Mo/ABC (57.3%) > 2Pd-5Zr/ABC (49.2%) > 2Pd-5W/ABC (45%) > 2Pd/ABC (42.9%). The maximum C9 phenolic monomer yield achieved in this study was similar to 22 wt%. The fractional conversion of lignin was 67-69% with Pd-metal oxide catalysts. The presence of Mo in the catalyst inhibited the hydrogenation of aliphatic C-alpha = C-beta in lignin and led to the formation of t-isoeugenol, while the presence of W and Zr resulted in selective formation of the hydrogenated product, propyl guaiacol. Using model compounds, it is proved that the formation of propyl guaiacol is via hydrogenation of t-isoeugenol, and not through dehydroxylation of propanol guaiacol. The dehydroxylation activity of the catalysts is attributed to the higher Lewis acidity and electropositive nature of the metals. A notable carbon atom economy of 47-50% towards total phenolic monomers was achieved with 2Pd/ABC, 2Pd-5Mo/ABC and 2Pd-5Zr/ABC catalysts.
Keywords: Activated biochar; Guaiacol; Hydrogenolysis; lignin; Metal oxides; Palladium